천장 은폐장소 전선관 연소에 따른 화재확산 및 피난 위험도에 관한 연구 - 박광묵(Kwang-Muk Park); 전재감(Jae-Kam Jeon); 방선배(Sun-Bae Bang) (한국화재소방학회 논문지, 2020)
In this study, the ISO 5660 and ISO 5659 combustion tests were conducted with synthetic resin conduits (CD, VE) and metal conduit (ST) used for wiring work in electrical facilities, which can be installed in ceiling concealed places. Then, fire spreading and evacuation risks were analyzed based on the measured data. In the ISO 5660 test, CD of 120.5 MJ/㎡, VE of 81.9 MJ/㎡, and ST of 4.9 MJ/㎡ were measured. In the ISO 5659 test, the CD 1320, VE 731, and ST 102 were measured, and then the maximum smoke densities were measured for CD 605 s, VE 740 s, and ST 1,200 s. In terms of fire spreading and evacuation risk, the CD conduit, VE conduit, and ST conduit were in order. In the fire spreading risk analysis, total heat emission was calculated as 4,820 MJ/㎡, 4,267 MJ/㎡, and 196 MJ/㎡ for CD, VE, and ST, respectively. Evacuation risk analysis shows at transmittance of 89%, CD is 127 s, VE is 35 s, and ST is 969 s. At transmittance of 79%, representing almost invisible concentration, CD is 157 s and VE is 50 s. The CD and VE conduits had a high fire spreading and evacuation risks, while the ST conduit had little effect on fire spreading and evacuation risk. 본 연구에서는 천장 은폐장소에 공사 가능한 전기설비 중 배선공사에 사용되는 합성수지관(CD, VE) 및 금속관(ST)을 대상으로 연소실험 및 ISO 5660 실험, ISO 5659 실험을 실시하였으며, 측정 데이터를 바탕으로 화재 확산 및 피난 위험도를 분석하였다. ISO 5660 총열방출량 실험결과 CD관 120.5 MJ/㎡, VE관 81.9 MJ/㎡, ST관 4.9 MJ/㎡이 측정되었다. ISO 5659 연기밀도 실험결과 CD관 1320, VE관 731, ST관 102이 측정되었으며, 최대연기밀도가 측정된 시간은 CD관 605 s, VE관 740 s, ST관 1,200 s이다. 화재 확산 및 피난 위험도에서 CD관, VE관, ST관 순으로 나타났다. 화재 확산 위험도 분석 시 총열방출량은 CD관 4,820 MJ/㎡, VE관 4,267 MJ/㎡, ST관 196 MJ/㎡로 산출되었다. 피난 위험도 분석결과 투과율 89% 때의 시간은 CD관 127 s, VE관 35 s, ST관 969 s, 거의 앞이 보이지 않을 정도의 농도를 나타내는 투과율 79% 때의 시간은 CD관 157 s, VE관 50 s로 나타났다. CD관과 VE관은 화재 확산 및 피난 위험도 수치가 높았던 반면 ST관의 경우 화재 확산에 거의 영향이 없었고, 피난 위험도에서도 화재발생 인지 후 피난하는데 문제가 없는 것으로 나타났다.